Дослідження міграції нафтопродуктів після техногенної аварії в м. Чернігові - Сємака, О.М.; Іванова, І.М.; Дзюба, В.А. (Екологічна безпека та природокористування, 2012)
Migration of oil products mixture after anthropogenic disaster at «Neftebasa» property of OJSC «Chernigovnefteproduct» (Chernigov, Ukraine) is examined having regard to the analysis of soil cover and oil products concentration.